Aβ Secretion and Plaque Formation Depend on Autophagy - Per Nilsson (Cell Reports, 2013)
Alzheimer’s disease (AD) is a neurodegenerative disease biochemically characterized by aberrant protein aggregation, including amyloid beta (Aβ) peptide accumulation. Protein aggregates in the cell are cleared by autophagy, a mechanism impaired in AD. To investigate the role of autophagy in Aβ pathology in vivo, we crossed amyloid precursor protein (APP) transgenic mice with mice lacking autophagy in excitatory forebrain neurons obtained by conditional knockout of autophagy-related protein 7. Remarkably, autophagy deficiency drastically reduced extracellular Aβ plaque burden. This reduction of Aβ plaque load was due to inhibition of Aβ secretion, which led to aberrant intraneuronal Aβ accumulation in the perinuclear region. Moreover, autophagy-deficiency-induced neurodegeneration was exacerbated by amyloidosis, which together severely impaired memory. Our results establish a function for autophagy in Aβ metabolism: autophagy influences secretion of Aβ to the extracellular space and thereby directly affects Aβ plaque formation, a pathological hallmark of AD.